Important features of linguocultureme in study of national and cultural words - Mirzayeva Gulbaxor Soxibovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Today, the connection between speech and culture is important in linguistics, and its field of study is expanding day by day. This article highlights the important aspects of linguacultural in the study of cultural and national features in the study of speech units.